Bleeding from Wharton's duct after fine‐needle aspiration biopsy on submandibular gland. Issue 11 (19th September 2018) - Lee, Dong Hoon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract : The case of a fine‐needle aspiration biopsy (FNAB) of the patient's salivary gland lesions is considered a rapid, simple, reliable, minimal invasive procedure with markedly rare complications. Herein, we report a case of bleeding from the region of the Wharton's duct after a procedure of a FNAB on the patient's submandibular gland. To our knowledge, this is the first case of bleeding from a salivary duct after a FNAB. For this reason, it is important to recognize that bleeding from the salivary duct after a FNAB can be a rare occurrence.